Location of a Chromosome Region Linked to Alternaria Brown Spot Resistance from the Evaluation of Triploid Mandarin Populations - Cuenca, José; Aleza, Pablo; Iborra, E.; Vicent, Antonio; Ollitrault, Patrick; Navarro, Luis (2017)
Alternaria brown spot (ABS) in citrus is a serious disease caused by the tangerine pathotype of the fungus Alternaria alternata, which induces necrotic lesions on fruit and young leaves, defoliation and fruit drop in susceptible genotypes. It is a strong concern for triploid breeding programs aiming to produce seedless mandarin cultivars. In the present work, we have taken advantage of the particular genetic structures of unreduced megagametophytes resulting from second division restitution (SDR) (leading to triploid hybrid recovery) to map a genome region linked to ABS resistance in citrus. The monolocus dominant inheritance of susceptibility, proposed on the basis of diploid population studies, was corroborated in triploid progeny. Bulk segregant analysis coupled with genome scan using a large set of genetically mapped SNP markers and targeted genetic mapping by half tetrad analysis, using SSR and SNP markers, allowed locating a region linked to ABS resistance near the centromere of chromosome III. SSR and SNP markers were developed for efficient early marker-assisted selection (MAS) of ABS resistant hybrids.